Peningkatan Produktivitas Belajar Santri Di Pesantren Melalui Konsep Personal Goal Setting - Yusuf, M.; Kholiq, Abdul; Ainun Nafiah, Lutfi; Jalil Jawhari, Abdul (LPPM Institut Al Azhar Menganti Gresik, 2023)
Islamic boarding schools (pesantren) play a crucial role in shaping the character and religious understanding of their students (santri). The challenge of improving learning productivity within pesantren is significant due to changes in learning patterns and the pressures of modern life. This research focuses on the concept of Personal Goal Setting (PGS) to enhance the learning productivity of santri. In this complex information era, PGS effectively helps santri establish personal goals, direct motivation, and improve learning performance. The aim of this research is to analyze the importance of PGS in enhancing the learning productivity of santri and its impact on academic achievement and character formation. The research method involves conducting library research by gathering data from various literature sources related to PGS, Islamic boarding school education, and factors influencing the learning productivity of santri. The analysis results reveal that PGS plays a significant role in improving the learning productivity of santri within pesantren, assisting in setting clear goals, motivating, and overcoming learning obstacles. It is recommended that pesantren take a more active approach in implementing PGS within their curriculum and in nurturing the character of santri, while also utilizing information technology to facilitate the monitoring of santri's learning goal achievements.